Level of polychlorinated biphenyls (PCBs) in selected marine fish (pelagic) from Straits of Malacca - Mohamad, Alina; Azlan, Azrina; Razman, Muhammad Rizal; Ramli, Nor Azam; Abdul Latiff, Aishah (Universiti Putra Malaysia Press, 2012)
Fish is a good source of protein, supply important vitamins and other essential nutrients including essential fatty acids (EFA), the EPA and DHA which help to reduce risk of death from coronary heart diseases. However, diet and food of animals’ origin are the most predominant sources of polychlorinated biphenyls (PCBs) to human which accounts to over 90%, with fish as one of the major routes of contaminants in human body. PCBs are a group of extremely stable aromatic chlorinated compounds which are relatively resistant to biological degradation and very persistent in the environment. This study has identified the type and level of 12 congeners of PCBs that are most toxic to humans. The maximum permitted level of PCBs in muscles meat of fish and fishery products is 4 pg/g, as recommended by World Health Organization (WHO) using the WHO-TEFs. Meanwhile, the highest amount of PCBs concentration was in Rastrelliger kanagurta (Indian mackerel), with the level of PCBs at 1.37 pg/g wet weight. Other species like Scomberomorus guttatus (Spanish mackerel), Pampus argenteus (Silver pompret), Megalapsis cordyla (Hardtail scad), Eleutheronema tradactylum (Fourfinger threadfin) and Chirocentrus dorab (Dorab wolfherring) showed PCBs levels ranging from 0.35 pg/g to 1.05 pg/g wet weight. Thus, the PCBs in all the samples were below the permitted level. It can be concluded that the studied pelagic fish are safe to consume. Although the levels were not high, it is still important to set limits for the PCBs in fish and shellfish species so as to make a better estimation of the risk of exposure to human through dietary intake of fish, specifically fatty fish to meet nutritional requirement for EPA and DHA.